2021
DOI: 10.3889/oamjms.2021.6378
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Interleukin 6 as a Predictor of Metabolic Syndrome in Schizophrenic Patients Receiving Combination Therapy of Typical and Atypical Antipsychotics

Abstract: BACKGROUND: Schizophrenia is a severe psychiatric disorder that causes disability and is often accompanied by physical illness. Based on the American Heart Association criteria, metabolic syndrome is common in schizophrenic patients, with a prevalence of 43% in Clinical Antipsychotic Trials of Intervention Effectiveness. The metabolic syndrome in patients with schizophrenia results from the side effects of antipsychotics. The metabolic syndrome will also show high levels of IL-6. This situation can have biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Significant increases of serum concentration of hs‐CRP were observed weekly after clozapine initiation. Among those studies examining other peripheral inflammatory markers, IL‐6 and TNFα are the most studied proinflammatory cytokines that were found to be elevated after clozapine treatment, 32–36 however, opposite changes 37,38 or no treatment effects 38–40 were also reported. Of note, elevated IL‐6 levels were consistently observed in patients who experienced fever during the initial phase of clozapine treatment, in comparison to those who did not develop fever (for further details, refer to monitoring of non‐specific signs and symptoms of inflammation section).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant increases of serum concentration of hs‐CRP were observed weekly after clozapine initiation. Among those studies examining other peripheral inflammatory markers, IL‐6 and TNFα are the most studied proinflammatory cytokines that were found to be elevated after clozapine treatment, 32–36 however, opposite changes 37,38 or no treatment effects 38–40 were also reported. Of note, elevated IL‐6 levels were consistently observed in patients who experienced fever during the initial phase of clozapine treatment, in comparison to those who did not develop fever (for further details, refer to monitoring of non‐specific signs and symptoms of inflammation section).…”
Section: Resultsmentioning
confidence: 99%
“…19 Significant increases of serum concentration of hs-CRP were observed weekly after clozapine initiation. Among those studies examining other peripheral inflammatory markers, IL-6 and TNFα are the most studied proinflammatory cytokines that were found to be elevated after clozapine treatment, [32][33][34][35][36] however, opposite changes 37,38 or no treatment effects [38][39][40] were also reported. Of note, elevated IL-6 levels were consistently observed in patients who experienced fever during the • Increases of multiple peripheral inflammatory markers were identified under the exposure of clozapine, including TNFα, IL-6, sTNF-Rs, and sIL-R, which were also associated with occurrence of fever.…”
Section: The Impact Of Clozapine On Inflammatory Markersmentioning
confidence: 99%
“…Risperidone can attenuate microglia activation in the brain, which may decrease IL-6 levels [26]. Serum IL-6 levels may also increase after 3 months of taking risperidone and clozapine in patients with the metabolic syndrome [40].…”
Section: Discussionmentioning
confidence: 99%
“…There are also markers of the metabolic syndrome occurring more frequently in patients with schizophrenia receiving atypical than typical combination therapy. 18 The 42 study subjects who received risperidone in both the treatment and control groups were measured for serum IL-6 levels at the baseline and the end of the 6th week. There was also a decrease in baseline IL-6 levels in the treatment group after six weeks with a difference of 3.61 pg/mL (p=0.001), while the control group on the baseline IL-6 with a difference of 2.46 pg/mL (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that antipsychotics can also alter the microbiota. There are also markers of the metabolic syndrome occurring more frequently in patients with schizophrenia receiving atypical than typical combination therapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%